Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka - Wickramasinghe, L. J. Mendis; Vidanapathirana, Dulan Ranga; Rathnayake, R. M. Gayan Priyankara (Zootaxa, 2016)
A new species of Cnemaspis, Cnemaspis rajakarunai sp. nov. is described and is the fourth rock dwelling species belonging to the genus known from Sri Lanka. The new species is readily distinguished from all other congeners by the following combination of characters: adult snout–vent length 36–40 mm; precloacal pores absent, large femoero-precloacal scales 22; femoral pores 7–8, enlarged femoral scales 6; ventral scales 146–186; supralabials (to midorbital position) 7; supralabials (to angle of jaws) 9; total lamellae on finger IV 19–22, shape of the basal lamellae on toe IV elliptical; and its unique colour pattern. The new species is recorded from Salgala Forest an unprotected lowland rain forest.